No Paragonimus in high-risk groups in Cote d'Ivoire, but considerable prevalence of helminths and intestinal protozoon infections - Traoré, S.G.; Odermatt, P.; Bonfoh, Bassirou; Utzinger, J.; Aka, N.D.; Adoubryn, K.D.; Assoumou, A.; Dreyfuss, G.; Koussemon, M. (Springer, 2011)
Background: Paragonimiasis is a neglected tropical disease caused by an infection with lung flukes that is transmitted through the consumption of undercooked crabs. The disease is often confused with tuberculosis. Paragonimiasis is thought to be endemic in south-western Côte d’Ivoire. Methods: Two cross-sectional surveys were carried out in the first half of 2009 in patients attending two tuberculosis centres of Abidjan. A third cross-sectional survey was conducted in May 2010 in children of two primary schools in Dabou, where crabs are frequently consumed. Patients with chronic cough provided three sputum samples plus one stool sample. Sputum samples were examined for tuberculosis with an auramine staining technique and for Paragonimus eggs using a concentration technique. Stool samples were subjected to the Ritchie technique. Schoolchildren provided a single stool sample, and samples were subjected to the Kato-Katz and an ether-concentration technique. A pre-tested questionnaire was administered to patients and schoolchildren to investigate food consumption habits. Additionally, between June 2009 and August 2010, shellfish were purchased from markets in Abidjan and Dabou and examined for metacercariae. Results: No human case of paragonimiasis was diagnosed. However, trematode infections were seen in 32 of the 272 shellfish examined (11.8%). Questionnaire results revealed that crab and pig meat is well cooked before consumption. Among the 278 patients with complete data records, 62 had tuberculosis, with a higher prevalence in males than females (28.8% vs. 13.9%, c2 = 8.79, p = 0.003). The prevalence of helminths and intestinal protozoa was 4.6% and 16.9%, respectively. In the school survey, among 166 children with complete data records, the prevalence of helminths and intestinal protozoa was 22.3% and 48.8%, respectively. Boys had significantly higher prevalences of helminths and intestinal protozoa than girls. Hookworm was the predominant helminth species and Entamoeba coli was the most common intestinal protozoon species (13.8%). Conclusions: Not a single case of Paragonimus was found in two high-risk groups of Côte d’Ivoire, most likely explained by food consumption habits. However, other helminth and intestinal protozoon infections were common.